-9(8-9m+n)=

Simple and best practice solution for -9(8-9m+n)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9(8-9m+n)= equation:


Simplifying
-9(8 + -9m + n) = 0
(8 * -9 + -9m * -9 + n * -9) = 0
(-72 + 81m + -9n) = 0

Solving
-72 + 81m + -9n = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '72' to each side of the equation.
-72 + 81m + 72 + -9n = 0 + 72

Reorder the terms:
-72 + 72 + 81m + -9n = 0 + 72

Combine like terms: -72 + 72 = 0
0 + 81m + -9n = 0 + 72
81m + -9n = 0 + 72

Combine like terms: 0 + 72 = 72
81m + -9n = 72

Add '9n' to each side of the equation.
81m + -9n + 9n = 72 + 9n

Combine like terms: -9n + 9n = 0
81m + 0 = 72 + 9n
81m = 72 + 9n

Divide each side by '81'.
m = 0.8888888889 + 0.1111111111n

Simplifying
m = 0.8888888889 + 0.1111111111n

See similar equations:

| 3x^3-4x^3= | | -4(7v-7)+5v=-87 | | 2x^2-20x+100=108 | | 5x+3y+2z=4 | | 2(10)+3y=24 | | 2(x+3y)+4(x+5y)-3x= | | (42+2x)=(3x+4) | | 2(10.4)+3y=24 | | -2(y-3)=-6y-12+2y | | 3a+12a=-7 | | 7.5a+9.2-6.8a-11b= | | -6(-1-3x)=-120 | | 9x^3+54x^2= | | 9x+3x=24 | | 4(2y-10)=3(2y+8) | | 3(5x+1)-2=3y+6 | | -2(y-3)=-6y-12+12y | | 4x-9y+3x= | | 3(y-10)+1=-5.5(y-8) | | X^2-5-35=0 | | -9(x-6)-4=50 | | -10x=-27x-17 | | x+3(1.25)=7.25 | | (4a-3b)(2a+6b)= | | 5xt-3xy= | | h(-0.5)=-4.5+3 | | y+.6=.8(y+2) | | y+.6=.8(y+2) | | Y=2b^2+4+9b | | [4x]=18+7y | | 2.3w+7+8.1+3w= | | 4.25*16= |

Equations solver categories